Epoxidised natural rubber - Baker C S L; Gelling I R; Samsuri Azemi Bin (Journal of Natural Rubber Research, 1986)
The reaction of natural rubber with periacids yields a new polymer, the properties of which depend on the degree of epoxidation. The epoxide groups are randomly distributed along the rubber backbone and this together with the steoro-specific nature of the epoxidation reaction and the relatively small size of the oxygen atom, result in a polymer than can strain crystallise and, hence has good strength properties. Hysteresis and resistance to hydrocarbon oils increase with the degree of epoxidation whereas air permeability decreases. At epoxide levels of 50 mole per ccnet, these properties are comparable to those of some of the speciality synthetic elastomers. Excellent reinforcement of epoxidised natural rubber is obtained with silica fillers, even in the absence of coupling agents. Two levels of epoxidation, 25 mole per cent (ENR-25) and 50 mole per cent (ENR-50), have been studied for their potential as commercial rubbers, and both are available as development materials.
Keywords: Epoxidised natural rubber; Natural rubber